Comparison of Inferior and Superior Conjunctival Autograft for Primary Pterygium. (August 2015) - Chen, Qi; Li, Yun; Xu, Fan; Yan, Yumei; Lu, Kewei; Cui, Ling; Li, Min
Abstract Purpose: To determine the postoperative symptom by using inferior conjunctival autografting (ICA) rather than superior conjunctival autografting (SCA) after excision of pterygium. Methods: This prospective randomized control study evaluated 80 eyes of 80 consecutive patients undergoing primary pterygium surgery. Patients in each subgroup were then randomized into the ICA (n = 40) or SCA (n = 40) group. All patients were asked to return for follow up on days 1, 2, 3, 5, 7, and 14 then at months 1, 3, 6, and 12 postoperatively. Outcome measures were postoperative patient discomfort, corneal epithelial healing time, complications and recurrence rate. Results: Fluorescein staining revealed complete corneal epithelial healing time was 3.1 ± 0.5 d (range 2–4) in the ICA group and 3.3 ± 0.6 d (range 2–4) in the SCA group (p = 0.11). Pain scores were significantly less in the ICA group than the SCA group on follow-up days 3 and 5 (p < 0.05). Postoperative foreign body sensation scores on follow-up days 5 and 7 were significantly lower in the ICA group than the SCA group (p < 0.05). Epiphora scores were significantly less in the ICA group than the SCA group on follow-up days 3, 5, and 7 (p < 0.05). No statistically significant differences between two groups were found for the overall (conjunctival and corneal) recurrence rates (5% versus 7.5%, p = 0.64). No serious complications were encountered. Conclusion: Pterygium excision with ICA led to less postoperative discomfort for patients with primary pterygium.